New Zealand Journal of Zoology - New Zealand Journal of Zoology (Taylor & Francis, 2026)
The New Zealand Journal of Zoology is an international journal publishing original scientific papers on all aspects of zoology. We welcome high-quality submissions from around the world that will make an impact on zoological research relevant to New Zealand and the entire Southern Hemisphere, the Pacific Rim and Antarctica. We strongly support early-career researchers.
FI 0.51
Q3
Keywords: Biological; Earth & Environmental Food Science; Zoología; Acuerdos transformativos; Transformative agreements; Biología de la conservación; Ecología; Taxonomía; Fisiología; Patología